Tinjauan Kuat Tekan Dan Kuat Lentur Dinding Panel Beton Ringan Dengan Perkuatan Tulangan Wiremesh - Hadma, Rossi Luluin; , Muhammad Ujianto, S.T., M.T; , Ir. Suhendro Trinugroho, M.T (2017)
The use of panel wall as an efficient and alternaltif technology innovation that initially using conventional brick wall that takes a many time in its application and has no reinforcement inside it. This study conducted a review of compressive strength and flexural strength of lightweight concrete panel wall with wiremesh strengthening reinforcement. Where coarse aggregate in the form of tile fragments with the average dimensions is 2 cm and the type of wiremesh reinforcement is M4, fabrication size diameter is 4 mm and circle is 15 cm x 15 cm. With the planned mix design using f.a.s 0.45 and the testing of panel wall is done when the age of a concrete wall panel is 28 days, because at the concrete age of 28 days, the concrete has reached optimum strength. The research using specimen such as concrete cylinders and panel wall in the form of concrete slab. Where the concrete cylinder with diameter dimensions of 15 cm and height of 30 cm amounted to 3 samples, obtained an average compressive strength of 14.504 MPa and an average concrete density of 2030 kg / m3 which are lighter than conventional concrete that average density is 2400 kg / m3, so that the coarse aggregate concrete in the form of tile fragments can be classified as lightweight concrete. And specimen panel wall with the dimensions of length is 100 cm, width is 50 cm, and thick is 7 cm, total is 15 samples with 5 samples without wiremesh strengthening reinforcement and 10 samples using wiremesh strengthening reinforcement. In the pressure test is gained an average compressive strength of 2,571 MPa (without reinforcement) and 2.897 MPa (with reinforcement), then it obtained an increase in the compressive strength of the panel wall of 12.68%. Then in the bending test is gained an average flexural strength of 1,728 MPa (without reinforcement) and 3.461 MPa (with reinforcement), then it obtained an increase in the flexural strength of the wall panel of 100.289%.